Labor Supply and Retirement Policy in an Overlapping Generations Model with Stochastic Fertility - Jorgensen, Ole Hagen (2012)
Using a stochastic general equilibrium model with overlapping generations, this paper studies a policy rule for the retirement age aiming at offsetting the effects on the supply of labor following fertility changes. The authors find that the retirement age should increase more than proportionally to the direct fall in labor supply caused by a fall in fertility. The robustness of this result is checked against alternative model specifications and parameter values. The efficacy of the policy rule depends crucially on the link between the preference for leisure and the response of the intensive margin of labor supply to changes in the statutory retirement age. The model has subsequently been calibrated for Brazil by Jorgensen (2010), in the context of the Brazil Aging Study.